Pelatihan Keterampilan Menulis Artikel Ilmiah Populer bagi Siswa SMAN 2 Tambang - Vera Sardila; Anggi Rosita Dewi; Afdhal Kusumanegara; Welli Marlisa; Rizki Erdayani; Nursalim; Ariyanti Rahayu (Sekolah Tinggi Ilmu Ekonomi Indonesia Jakarta, 2026)
Twenty-first century literacy requires students to think critically, creatively, and communicate ideas effectively through writing. However, a needs assessment at SMAN 2 Tambang revealed that students experienced difficulties in understanding the concept of popular scientific articles, developing ideas, constructing evidence-based arguments, and applying effective written language. This community service program aimed to improve students’ knowledge and writing skills through practice-based training and mentoring. The activity was conducted on January 21, 2026, at SMAN 2 Tambang, Kampar Regency, Riau, involving 20 students. The program included lectures, discussions, structured writing exercises, hands-on practice, and mentoring. Evaluation was carried out through observation and assessment of participants’ written work. The results showed that all participants completed the program. A total of 85% understood the concept of popular scientific articles, 85% were able to determine appropriate topics and writing perspectives, 80% successfully produced article drafts, and 90% demonstrated active participation and high motivation. The program effectively enhanced students’ writing competence and supported the development of a literacy culture in schools.